2017
DOI: 10.33549/physiolres.933313
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Hemodynamics: Mayer Waves in Different Phases of Ovarian and Menstrual Cycle in Women

Abstract: The goal of the research is to investigate the special effect of ovarian-menstrual cycle phases on the level of women’s blood pressure and characteristics of Mayer waves. 77 women aged 18-19 were tested under condition close to the state of basal metabolism in follicular phase (I), ovulation (II) and luteal phase (III) of ovarian-menstrual cycle. In phases II and III, the increase of mean and diastolic blood pressure level, in comparison with phase I in the prone position at rest and with psycho-emotional load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…On the basis of studying and processing the research data of the other authors (Bouchard, 2012, Kipp, 2017, Lutsenko, Kоvalenko, 2017 and according to the results of our study, it was found that the motivational interest of students of different institutions of higher education (non-sport specialties) in physical education classes is extremely low (Cline, Gammage, 2015, Han, Gabriel, Kohl, 2017, Zarei, Memari, Moshayedi, Mosayebi, Mansournia, Khoo, Morris, 2016). It directly affects health and disability.…”
Section: Discussionmentioning
confidence: 65%
“…On the basis of studying and processing the research data of the other authors (Bouchard, 2012, Kipp, 2017, Lutsenko, Kоvalenko, 2017 and according to the results of our study, it was found that the motivational interest of students of different institutions of higher education (non-sport specialties) in physical education classes is extremely low (Cline, Gammage, 2015, Han, Gabriel, Kohl, 2017, Zarei, Memari, Moshayedi, Mosayebi, Mansournia, Khoo, Morris, 2016). It directly affects health and disability.…”
Section: Discussionmentioning
confidence: 65%
“…(Kyiv Research Institute of Radio-measuring Equipment). The spring electrodes of rheograms were standardized [10]. The frequency of the reagent's probe signal was 70 kHz.…”
Section: Circumstancesmentioning
confidence: 99%
“…The digital signals were stored on the hard disk of the computer for further processing. To analyze signals, identify critical points on them, and export them to spreadsheets, Bioscan [10] was used.…”
Section: Circumstancesmentioning
confidence: 99%
See 2 more Smart Citations